2021
DOI: 10.1186/s12884-021-04123-7
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and predictors of fear of childbirth among pregnant Chinese women: a hierarchical regression analysis

Abstract: Background Fear of childbirth (FOC) occurs before, during and after pregnancy and is harmful to both the pregnant woman and the fetus. Identifying the prevalence and predictors of FOC can help us generate strategies for alleviating women’s FOC. Methods A cross-sectional study was conducted among a convenience sample of 646 pregnant women receiving antenatal care at a subordinate hospital of a university in China. Data were collected using a basic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 72 publications
(138 reference statements)
6
21
0
Order By: Relevance
“…Our study identified that primiparas, unplanned pregnancy, and little spousal support were significant risk factors in FOC. In line with previous research ( 2 , 44 , 57 ), primiparity was one of the significant predictors of severe FOC. In contrast, one Finland population-based analysis suggested that multiparous women also tended to have fear of childbirth for previous cesarean section, preterm birth, and unspecified socioeconomic status ( 58 ).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our study identified that primiparas, unplanned pregnancy, and little spousal support were significant risk factors in FOC. In line with previous research ( 2 , 44 , 57 ), primiparity was one of the significant predictors of severe FOC. In contrast, one Finland population-based analysis suggested that multiparous women also tended to have fear of childbirth for previous cesarean section, preterm birth, and unspecified socioeconomic status ( 58 ).…”
Section: Discussionsupporting
confidence: 90%
“…According to previous reviews and research (2,10,11,(42)(43)(44), age, parity, gestational weeks, and spousal support were associated with FOC. Thus, the exploratory analysis was first conducted to clarify the relationships between sociodemographic and obstetric factors and FOC.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations